EFFECT OF STRUCTURAL HEAT CONDUCTION ON THE PERFORMANCE OF MICRO-COMBUSTORS AND MICRO-THRUSTERS - Leach, Timothy (My University, 2005)
This thesis investigates the effect of gas-structure interaction on the design and performance of miniaturized combustors with characteristic dimensions less than a few millimeters. These are termed 'micro-combustors' and are intended for use in devices ranging from micro-scale rocket motors for micro, nano, and pico-satellite propulsion, to micro-scale engines for micro-Unmanned Air Vehicle (UAV) propulsion and compact power generation. Analytical models for the propagation of a premixed laminar flame in a micro-channel are developed. The models' predictions are compared to the results of more detailed numerical simulations that incorporate multi-step chemistry, distributed heat transfer between the reacting gas and the combustor structure, heat transfer between the combustor and the environment, and heat transfer within the combustor structure. The results of the modeling and simulation efforts are found to be in good qualitative agreement and demonstrate that the behavior of premixed laminar flames in micro-channels is governed by heat transfer within the combustor structure and heat loss to the environment. The key findings of this work are as follows: First, heat transfer through the micro-combustor's structure tends to increase the flame speed and flame thickness. The increase in flame thickness with decreasing passage height suggests that micro-scale combustors will need to be longer than their conventional-scale counterparts. However, the increase in flame speed more than compensates for this effect and the net effect is that miniaturizing a combustor can increase its power density substantially. Second, miniaturizing chemical rocket thrusters can substantially increase thrust/weight ratio but comes at the price of reduced specific impulse (i.e. overall efficiency). Third, heat transfer through the combustor's structure increases steady-state and transient flame stability. This means that micro-scale combustors will be more stable than their conventional-scale counterparts. Fourth and finally, the extended temperature profile associated with the broadened flame causes a different set of elementary reactions to dominate the operation of the overall reaction mechanism at the micro-scale. This suggests that new chemical mechanisms may need to be developed in order to accurately simulate combustion at small-scales. It also calls into question the efficacy of single-step mechanisms presently used by other researchers.
Keywords: Engineering, Aerospace; Micro-combustion; Micro-propulsion; MEMS; Heat-Recirculating Combustor; Flame Broadening; Flame stability